Pemetaan Sebaran Tempat Pembuangan Sampah (TPS) Ilegal Di Wilayah Pengembangan V Kota Pekanbaru - Daniel Ilham Wahyudi; Jecky Asmura; David Andrio (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Development Region V consists of Marpoyan Damai District, TampanDistrict, and Payung Sekaki District, with an area of 140,96 km2 and a population of 510,107 people. In 2016, the waste generated from this development area settlement was 1,049,179 l/day. The development region V with high data on population and waste generation per day is the biggest contributor to waste and if the management of the waste is not optimal that will cause the existence of illegal dumping increased.The purpose of this study is to map and analyze geophysical, anthropogenic and community characteristics. This research was conducted with a direct survey methodto the study area with GPS Garmin 60CSx type, then mapped using GIS software, ArcMap 10.1. In the V development region, 33 locations of illegal dumping werefound. There were no illegal dumping found at a distance of ≤ 15 m from the river. In the distance parameters of arterial and local roads, the existence of illegal dumpingis generally located at a distance of <5 m or at the shoulder of road, that can caused by the accessibility or of the community to dispose of garbage to that location easily.For the land type, mostly the community will be waste disposal on the main road. On the road type parameters Illegal dumping, commonly were found on arterial roadsbecause the service center for transporting garbage is generally on arterial roads. The insufficient number of legal dumping causes the number of illegal dumping increased. The number of illegal dumping increases with the high population density.The level of education and knowledge will influence attitudes and behavior of waste management, because low levels of education and lack of knowledge will improve unhealthy attitudes and behavior. The number of illegal dumping increased with theincrease in the number of respondents with the type of work of traders.Keyword: Geographic Information System(GIS), Illegal Dumping, ArcMap, Mapping of Illegal Dumping